HARMONISED CONDITIONS FOR THE MARKETING OF CONSTRUCTION PRODUCTS IN THE SINGLE EUROPEAN MARKET (Innovation in Woodworking Industry and Engineering design, 2026)
The free movement of goods is the cornerstone of the single market. The mechanisms that are necessary to achieve this goal are based on prevention of technical obstacles to trade, on mutual recognition and on technical harmonisation.In order to improve the functioning of the internal market in construction products, in May 2008 the European Commission proposed replacing the Directive on Construction Products (89/106/EEC) with a new regulation intended to eliminate the still existing reg-ulatory and technical obstacles to the free movement of construction products in the European Economic Area.The new Regulation laying down harmonised conditions for the marketing of construc-tion products was adopted by the European Parliament and the Council on 9 March 2001. The Regulation repeals the so far effective Directive 89/106/EEC on Construction Products and enters into force 20 day following its publication in the Official Journal of the European Un-ion on 04.04.2011, i.e. on 24.04.2011. After this date, it becomes binding and shall be applied directly in all Member States.It is necessary that the manufacturers of wood-based products are made acquainted in time with the novelties in this field because a great part of their produce is put into construction sites and comes under the scope of the European technical legislation.A review of the main requirements of Regulation No. 305/2011 laying down harmonised conditions for the marketing of construction products has been made in the paper.